SISTEM INFORMASI PENYEBARAN PENGUMUMAN DAN REMINDER LAYANAN AKADEMIK SMK ISLAM KALIPARE BERBASIS WEB DENGAN NOTIFIKASI WHATSAPP MENGGUNAKAN METODE USER CENTERED DESIGN - Tania Putri Pratama; Hari Lugis Purwanto; Rini Agustina (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2026)
Distributing academic service announcements and reminders is a crucial component in supporting the smooth running of academic activities at school. However, the process of delivering academic announcements at Kalipare Islamic Vocational School is still carried out conventionally and manually through notice boards, circulars, and WhatsApp groups. This method often causes various problems, such as late announcements, unread announcements, and the risk of students and parents or guardians not receiving announcements on time, especially when students are absent from school. This condition indicates the need for an information system capable of delivering announcements centrally, quickly, and consistently. This study aims to design and build a Web-Based Information System for Distributing Academic Service Announcements and Reminders with WhatsApp Notifications at Kalipare Islamic Vocational School. The development method used is User-Centered Design (UCD) by directly involving users in every stage of system development, from needs analysis to system evaluation. The developed system allows administrators and teachers to create and manage academic announcements and reminders through a web-based platform, which must then obtain approval or revision from the principal before being sent to students and parents or guardians via WhatsApp notifications. The system is also equipped with features for managing student data, department data, class data, message templates, and an announcement log as a history of announcement distribution. The system was tested using the User Acceptance Testing (UAT) method involving 20 respondents. The test results showed that all tested features were accepted by users using the User Acceptance Testing (UAT) method, thus the system has been assessed as meeting the research objectives and capable of improving the effectiveness and timeliness of the distribution of announcements and reminders for academic services.